Cryo-EM structure of the bacteria-killing type IV secretion system core complex from Xanthomonas citri. (December 2018) - Sgro, Germán; Costa, Tiago; Cenens, William; Souza, Diorge; Cassago, Alexandre; Coutinho de Oliveira, Luciana; Salinas, Roberto; Portugal, Rodrigo; Farah, Chuck; Waksman, Gabriel
Abstract Type IV secretion (T4S) systems form the most common and versatile class of secretion systems in bacteria, capable of injecting both proteins and DNAs into host cells. T4S systems are typically composed of 12 components that form 2 major assemblies: the inner membrane complex embedded in the inner membrane and the core complex embedded in both the inner and outer membranes. Here we present the 3.3 Å-resolution cryo-electron microscopy model of the T4S system core complex fromXanthomonas citri, a phytopathogen that utilizes this system to kill bacterial competitors. An extensive mutational investigation was performed to probe the vast network of protein–protein interactions in this 1.13-MDa assembly. This structure expands our knowledge of the molecular details of T4S system organization, assembly and evolution. A combination of cryo-electron microscopy (cryo-EM) and targeted mutagenesis studies elucidates the structure and organization of the core complex of the type IV secretion system used byXanthomonas citri to kill competing bacteria.